PERANCANGAN SISTEM INFORMASI GRAFIK BARBER JOHNSON DALAM MENGUKUR EFISIENSI RUMAH SAKIT MENGGUNAKAN MICROSOFT VISUAL STUDIO 2013 - M Luthfi Fauzi; Yuda Syahidin; Syaikhul Wahab (POLITEKNIK PIKSI GANESHA, 2021)
The purpose of this research is to design an information systems johson barber graphs using Microsoft visual studio 2013 at RSUD Sumedang. The research method used qualitative descriptive method with design model, while data collection techniques with observation, interview and literature study. Based on research done, information systems Johnson barber graphs is still manually. Therefore the new system created with Microsoft Visual Studio 2013, using My Sql database, using the software development waterfall model, so the user in this case is the officer, just simply input data in the form that has been provided and the data can be directly in the process so get desired results. The suggestions provided are: 1) making computerized Johnson barber graphs information systems, which can reduce weaknesses during implementation of the manual systems, and 2) planning maintenance and care sustainable development of the system. Keyword: Information Systems, Johnson Barber Graphs, Microsoft Visual Studio 2013